Lignin-derived carbon material for electrochemical energy storage applications: Insight into the process-structure-properties-performance correlations - Li, Wenqi; Shi, Jian (Frontiers in Bioengineering and Biotechnology, 2023)
As increasing attention has been paid to applications of lignin-derived energy storage materials in the last decade, most studies pursue the improvement of electrochemical performance obtained from novel lignin sources, or structure and surface modifications of synthesized materials, while the study on the mechanisms of lignin thermochemical conversion is rare. This review emphasizes on establishing a process-structure-properties-performance correlation across multiple key aspects associated with valorizing lignin from a byproduct of biorefineries to high performance energy storage materials. Such information is the key to a rationally designed process for the low-cost production of carbon materials from lignin.